Gold(I)-catalyzed hydroxy group assisted C(sp(2))-H alkylation of enaminones with diazo compounds to access 3-alkyl chromones - Bagle, Pradip N.; Mane, Manoj V.; Sancheti, Shashank P.; Gade, Amol B.; Shaikh, Samir R.; Baik, Mu-Hyun; Patil, Nitin T. (Organic Letters, 2019)
A strategy for expedient synthesis of 3-substituted chromones from easily available o-hydroxyarylenaminones and diazo compounds has been developed. Carefully conducted experimental and computational studies led us to propose an uncommon mechanistic pathway involving the hydroxyl group assisted alkylation of enaminones with in situ generated gold carbenes.

Ortho-oxygenative 1,2-difunctionalization of diarylalkynes under merged gold/organophotoredox relay catalysis - Sancheti, Shashank P.; Akram, Manjur O.; Roy, Rupam; Bedi, Vaibhav; Kundu, Shubhankar; Patil, Nitin T. (Chemistry-An Asian Journal, 2019)
Reported herein is an ortho-oxygenative 1,2-difunctionalization of diarylalkynes under merged gold/organophotoredox catalysis to access highly functionalized 2-(2-hydroxyaryl)-2-alkoxy-1-arylethan-1-ones. Detailed mechanistic studies suggested a relay process, initiating with gold-catalyzed hydroalkoxylation of alkynes, to generate enol-ether followed by a key formal [4+2]-cycloaddition reaction. The successful application of the present methodology was also shown for the synthesis of benzofurans.
Keywords: binary catalyst system; Gold catalysis; organocatalyst; photoredox; synthetic methodology

BQ-AurIPr: a redox-active anticancer Au(i) complex that induces immunogenic cell death - Mule, Ravindra D.; Kumar, Akhilesh; Sancheti, Shashank P.; Senthilkumar, B.; Kumar, Himanshu; Patil, Nitin T. (Chemical Science, 2022)
Immunogenic Cell Death (ICD) is a unique cell death mechanism that kills cancer cells while rejuvenating the anticancer immunosurveillance, thereby benefiting the clinical outcomes of various immuno-chemotherapeutic regimens. Herein, we report development of a library of benzo[a]quinolizinium-based Au(i) complexes through an intramolecular amino-auration reaction of pyridino-alkynes. We tested 40 candidates and successfully identified BQ-AurIPr as a novel redox-active Au(i) complex with potent anticancer properties. BQ-AurIPr efficiently triggered generation of DAMPs - the hallmarks of ICD - and was superior in terms of efficiency compared to FDA-approved drugs known to induce ICD. BQ-AurIPr significantly increased immunogenicity of cancer cells enhancing their phagocytosis when co-cultured with immune cells. Our investigation reveals that BQ-AurIPr induces oxidative stress inside mitochondria leading to mitophagy, as the mechanism for immunogenic cell death in A549 cells.

Interplay of anion-pi(+) and pi(+)-pi(+) interactions in novel pyrido[2,1-a]isoquinolinium-based aiegens - substituent- and counterion-dependent fluorescence modulation and applications in live cell mitochondrial imaging - Mule, Ravindra D.; Roy, Rupam; Mandal, Koushik; Chopra, Deepak; Dutta, Tanoy; Sancheti, Shashank P.; Shinde, Popat S.; Banerjee, Somsuvra; Lal Koner, Apurba; Bhowal, Rohit; Senthilkumar, Beeran; Patil, Nitin T. (Chemistry-A European Journal, 2022)
Recently, the concept of anion-pi(+) interactions has witnessed unique applications in the field of AIEgen development. In this contribution, we disclose a consolidated study of a library of N-doped ionic AIEgens accessed through silver-mediated cyclization of pyridino-alkynes. A thorough photophysical, computational and crystallographic study has been conducted to rationalize the observed substituent- and counterion-dependent fluorescence properties of these luminogens. We further elucidate the prominent role of anion-pi(+) interactions, pi(+)-pi(+) interactions and other non-covalent interactions, in inhibiting the undesired ACQ effect. Finally, we have also demonstrated the application of selected AIEgens for imaging of mitochondria in live cells.
Keywords: 1-a]isoquinolinium; AIEgens; anion-pi(+); crystal structure; mitochondrial imaging; pyrido[2